2005
DOI: 10.4049/jimmunol.174.8.4736
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Kvβ Subunit Expression in Macrophages Depends upon Proliferation and the Mode of Activation

Abstract: Voltage-dependent potassium channels (Kv) in leukocytes are involved in the immune response. In bone marrow-derived macrophages (BMDM), proliferation and activation induce delayed rectifier K+ currents, generated by Kv1.3, via transcriptional, translational, and posttranslational controls. Furthermore, modulatory Kvβ subunits coassociate with Kvα subunits, increasing channel diversity and function. In this study we have identified Kvβ subunits in mouse BMDM, studied their regulation during proliferation and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 52 publications
3
62
0
Order By: Relevance
“…Transient transfection was performed using Lipofectamine 2000 (Invitrogen) at nearly 80% confluence. Twenty-four hours after transfection, the cells were washed in phosphate-buffered saline (PBS), fixed, and mounted with Aqua Poly/Mount from Polysciences, Inc. Murine bone marrow-derived macrophages from 6 -10-week-old BALB/c mice (Charles River laboratories) were isolated and cultured as described elsewhere (7,12,19). Briefly, the animals were killed by cervical dislocation, and both femurs were dissected with the adherent tissue removed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transient transfection was performed using Lipofectamine 2000 (Invitrogen) at nearly 80% confluence. Twenty-four hours after transfection, the cells were washed in phosphate-buffered saline (PBS), fixed, and mounted with Aqua Poly/Mount from Polysciences, Inc. Murine bone marrow-derived macrophages from 6 -10-week-old BALB/c mice (Charles River laboratories) were isolated and cultured as described elsewhere (7,12,19). Briefly, the animals were killed by cervical dislocation, and both femurs were dissected with the adherent tissue removed.…”
Section: Methodsmentioning
confidence: 99%
“…This is important in leukocytes where Kv1.3 and rafts concentrate at the immunological synapse, and raft composition regulates Kv1.3-related cellular functions (16 -18, 28). Unlike T-lymphocytes, macrophages express Kv1.3 and Kv1.5 channels (7,12,13,19). Raft extractions showed that, although Kv1.3 colocalized partially with caveolin (12 Ϯ 2%), Kv1.5 did not target to lipid rafts (Fig.…”
Section: Kv15 Modifies Kv13 Mobility At the Cell Surface-mentioning
confidence: 99%
See 1 more Smart Citation
“…Murine bone marrow-derived macrophages (BMDM) were isolated as described elsewhere [2,21]. Cells were cultured in DMEM containing 20% FBS and 30% supernatant of L-929 fibroblast (L-cell) conditioned media as a source of MacrophageColony Stimulating Factor (MCSF).…”
Section: Animals and Cell Culturementioning
confidence: 99%
“…The differences in the timing of mRNA transcription resulted in electrophysiological differences. Furthermore, they recorded evidence of the impact of differential expression of Kv subunits in macrophages during proliferation and differential activation between LPS and TNF- (Vicente et al, 2005). The expression of Kv1.5 resulted in associations with Kv1.3 to conform hetero-dimers to distinct biophysical properties (Vicente et al, 2006;Vicente et al, 2007).…”
Section: Macrophage Ion Currentsmentioning
confidence: 99%